2018
DOI: 10.1111/tid.12938
|View full text |Cite
|
Sign up to set email alerts
|

Donor‐derived multiorgan transmission of mixed P. malariae and P. ovale infection: Impact of globalization on post‐transplant infections

Abstract: A 57-year-old man was admitted with fever and thrombocytopenia 1 month after renal transplantation. He had never received a blood transfusion or travelled outside Spain. A peripheral blood smear revealed Plasmodium malariae and P. ovale parasites, diagnosis confirmed later by malaria PCR. The donor, from Equatorial Guinea, had negative thick and thin blood smears and rapid malaria antigen test prior to organ donation. Peripheral blood malaria PCR was not performed during donor screening. The second renal recip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…For these reasons, reports of malaria infection following transplantation are not surprising. Indeed, Martín-Dávila et al[96] recently reported patients infected by P. malariae and P. ovale after liver and kidney transplantations. Parasite transmission can also occur after BM transplantation as described in a recent case even when the donor was not classified at risk[97].…”
Section: Stem Cell and Parasite Therapiesmentioning
confidence: 99%
“…For these reasons, reports of malaria infection following transplantation are not surprising. Indeed, Martín-Dávila et al[96] recently reported patients infected by P. malariae and P. ovale after liver and kidney transplantations. Parasite transmission can also occur after BM transplantation as described in a recent case even when the donor was not classified at risk[97].…”
Section: Stem Cell and Parasite Therapiesmentioning
confidence: 99%
“…Even with the use of the most sensitive diagnostic test on blood, liver transplantation has been associated with the transmission of P. vivax due to the persistence of hepatic hypnozoites, which is also possible for P. ovale [112,113]. Several cases of multi-organ transmission of malaria from a single donor have been described [107,114,115].…”
Section: Donor Deferral and Screeningmentioning
confidence: 99%
“…Post-transplant malaria presents with high fever and chills that do not respond to empirical antibiotic therapy [107,114,115,[118][119][120][121]; thrombocytopenia and anemia are commonly observed as in the case of vector-borne malaria [114,115,[118][119][120][121]. Mental impairment, coma, or acute renal failure may be observed as complications of P. falciparum malaria when the diagnosis is delayed [115,118,119].…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of transfusion-transmitted malaria (TTM) in malaria endemic sub-Saharan regions is estimated between 14 and 28% [22]. Several reports describe that P. falciparum [22], P. vivax [23], P. malariae [24], P. knowlesi [25] and P. ovale [26] can be transmitted either through blood donations or solid organ transplantations.…”
Section: Introductionmentioning
confidence: 99%